Constitutionalism facing the challenge of integration in the ECOWAS region : contribution to the study of the protection of fundamental rights since the "democratic opening" in Africa - (:unkn) unknown (My University, 2018)
The study of constitutionalism in the legal order of the Economic Community of West African States (ECOWAS), through the lens of the protection of fundamental rights, seems particularly interesting, such that the West African organization has undergone a profound transformation or even metamorphosis. From an economic point of view, ECOWAS has transcended it’s initial dimension to achieve supranationality, the only way to the proven effectiveness that will allow it both to seize it’s community ambition and not miss the meeting of globalization. This is evidenced by the ever-increasing constitutionalization of the Community legal order by a Praetorian method of protecting fundamental rights, which has enable the ECOWAS Court of Justice to establish it’s autonomy. However, constitutionalism does not seem to penetrate definitely the West African legal order which is only in it’s embryonic stage. Nevertheless, in the face of demands of an African democratic renewal, it was necessary to turn resolutely towards the creation of a legal and political environment conducive to the realization of the African integration project. In order to better define the community’s conviction and definitively enshrine the renewal of regionalism, the Member States had to abandon their unreasoned theoretical ambition, based on developmentalism, to guarantee the process of integration, the essential elements for the construction of it’s "identity", in particular it’s "constitutional identity". In that respect, the normative evolution of ECOWAS, first initiated by the Revised Treaty, then by the Protocol on Democracy and Good Governance and finally the Accra Protocol relating to the Court of Justice, has made it possible to determine the constitutional framework of the Community. These are fundamental evolutions which have allowed both the legalization of fundamental rights and the affirmation of West African constitutionalism. These principles of constitutional con
Keywords: African Research